2013
DOI: 10.1016/j.braindev.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Parenting-related stress and psychological distress in mothers of toddlers with autism spectrum disorders

Abstract: Background Parents of children with autism spectrum disorders (ASDs) are at risk for higher stress levels than parents of children with other developmental disabilities and typical development. Recent advances in early diagnosis have resulted in younger children being diagnosed with ASDs but factors associated with parent stress in this age group are not well understood. Aims The present study examined parenting-related stress and psychological distress in mothers of toddlers with ASD, developmental delay wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
231
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(263 citation statements)
references
References 29 publications
23
231
1
8
Order By: Relevance
“…Parents of children with ASD experience higher levels of parenting stress than parents of typically developing children (e.g., Duarte et al 2005;Hayes and Watson 2012;Hoffman et al 2009;Rao and Beidel 2009) as well as parents of children with other developmental disabilities (e.g., Estes et al 2009Estes et al , 2012Schieve et al 2007Schieve et al , 2011. This is concerning given that high levels of parenting stress are associated with diminished child outcomes over time following intervention (Osborne et al 2008a, b).…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…Parents of children with ASD experience higher levels of parenting stress than parents of typically developing children (e.g., Duarte et al 2005;Hayes and Watson 2012;Hoffman et al 2009;Rao and Beidel 2009) as well as parents of children with other developmental disabilities (e.g., Estes et al 2009Estes et al , 2012Schieve et al 2007Schieve et al , 2011. This is concerning given that high levels of parenting stress are associated with diminished child outcomes over time following intervention (Osborne et al 2008a, b).…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…Moreover, it has been suggested that children's relationship with their parents is more effective than their relationship with their teachers in terms of their adaptation to the preschool environment (Pianta, Nimetz, & Bennett, 1997). In particular when it comes to evaluating preschool children's deficiencies, parents play a key role in contributing to the development of their children by selecting appropriate remedial educational programs (Bloch & Weinstein, 2009;Estes et al, 2013). The parent form of the Preschool Children's Communication Skills Scale is considered beneficial for identifying children's fundamental communication skills and preparing suitable educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between difficult childhood behavior and caregiver frustration and dissatisfaction [28,32]. Developmental disability in a child can also have a significant impact on caregiver stress [33,34], often resulting in severe complications in the caregivers' primary relationship [35,36]. In summary, maladaptive characteristics in children are a major factor in caregiver stress [37].…”
Section: Instrumentsmentioning
confidence: 99%